Ageing changes in biventricular cardiac function in male and female baboons (Papio spp.). (19th September 2018) - Kuo, Anderson H.; Li, Cun; Huber, Hillary F.; Nathanielsz, Peter W.; Clarke, Geoffrey D.
Abstract : Key points: Life course changes in cardiovascular function in a non‐human primate have been comprehensively characterized. Age‐related declines in normalized left ventricular stroke volume and cardiac output were found with corresponding decreases in biventricular ejection fractions and filling rates. There were age‐related decreases in male and female baboon normalized left ventricular myocardial mass index, which declined at similar rates. Systolic functional declines in right ventricular function were observed with age, similar to the left ventricle. Sex differences were found in the rates and directions of right ventricular volume changes along with decreased end‐systolic right ventricular sphericity. The results validate the baboon as an appropriate model for translational studies of cardiovascular functional decline with ageing. Abstract: Previous studies reported cardiac function declines with ageing. This study determined changes in biventricular cardiac function in a well‐characterized baboon model. Cardiac magnetic resonance imaging measured key biventricular parameters in 47 baboons (22 female, age 4–23 years). ANCOVA assessed sex and age changes with P < 0.05 deemed significant. Stroke volume, cardiac output and other cardiac functional parameters were normalized to body surface area. There were similar, age‐related rates of decrease in male (M) and female (F) normalized left ventricular (LV) myocardial mass index (M: −1.2 g m −2 year −1, F: −0.9 g m −2 year −1 ). LV ejection fraction declined at −0.96% year −1 ( r = −0.43, P = 0.002) and right ventricular (RV) ejection fraction decreased at −1.2% year −1 ( r = −0.58, P < 0.001). Normalized LV stroke volume fell at −1.1 ml m −2 year −1 ( r = −0.47, P = 0.001), normalized LV ejection rate at −3.8 ml s −1 m −2 year −1 ( r = −0.43, P < 0.005) and normalized LV filling rate at −4.1 ml s −1 m −2 year −1 ( r = −0.44, P < 0.005). Also, RV wall thickening fraction decreased with age (slope = −1% year −1, P = 0.008). RV ejection rate decreased at −3.6 ml s −1 m −2 year −1 ( P = 0.002) and the normalized average RV filling rate dropped at −3.7 ml s −1 m −2 year −1 ( P < 0.0001). End‐systolic RV sphericity index also dropped with age ( r = −0.33, P = 0.02). Many observed changes parallel previously reported data in human and animal studies. These measured biventricular functional declines in hearts with ageing from the closest experimental primate species to man underscore the utility of the baboon model for investigating mechanisms related to heart ageing. Key points: Life course changes in cardiovascular function in a non‐human primate have been comprehensively characterized. Age‐related declines in normalized left ventricular stroke volume and cardiac output were found with corresponding decreases in biventricular ejection fractions and filling rates. There were age‐related decreases in male and female baboon normalized left ventricular myocardial mass index, which declined at similar rates. Systolic functional declines in right ventricular function were observed with age, similar to the left ventricle. Sex differences were found in the rates and directions of right ventricular volume changes along with decreased end‐systolic right ventricular sphericity. The results validate the baboon as an appropriate model for translational studies of cardiovascular functional decline with ageing.